Khat use, PTSD and psychotic symptoms among Somali refugees in Nairobi - a pilot study - Marina eWidmann; Abdulkadir Hussein eWarsame; Jan eMikulica; Johannes evon Beust; Maimuna Mohamud eIsse; David eNdetei; David eNdetei; Mustafa eal'Absi; Michael eOdenwald; Michael eOdenwald (Frontiers Media S.A., 2014)
In East-African and Arab countries, khat leaves are traditionally chewed in social settings. They contain the amphetamine-like alkaloid cathinone. Especially among Somali refugees khat use has been associated with psychiatric symptoms. We assessed khat use patterns and psychiatric symptoms among male Somali refugees living in a disadvantaged urban settlement area in Kenya, a large group that has not yet received scientific attention. We wanted to explore consume patterns and study the associations between khat use, traumatic experiences and psychotic symptoms. Using privileged access sampling we recruited 33 healthy male khat chewers and 15 comparable non-chewers. Based on extensive preparatory work, we assessed khat use, khat dependence according to DSM-IV, traumatic experiences, Posttraumatic Stress Disorder and psychotic symptoms using standardized diagnostic instruments that had been adapted to the Somali language and culture. Hazardous use patterns like chewing for more than 24 hours without interruption were frequently reported. All khat users fulfilled the DSM-IV-criteria for dependence and eighty-five percent reported functional khat-use, i.e. that khat helps them to forget painful experiences. We found that the studied group was heavily burdened by traumatic events and posttraumatic symptoms. Khat users had experienced more traumatic events and had more often PTSD than non-users. Most khat users experience khat-related psychotic symptoms and in a quarter of them we found true psychotic symptoms. In contrast, among control group members no psychotic symptoms could be detected. We found first evidence for the existence and high prevalence of severely hazardous use patterns, comorbid psychiatric symptoms and khat use as a self-medication of trauma-consequences among male Somali refugees in urban Kenyan refugee settlements. There is a high burden by psychopathology and adequate community-based interventions urgently need to be developed.